Surrogate Virus Neutralisation Test Based on Nanoluciferase-Tagged Antigens to Quantify Inhibitory Antibodies against SARS-CoV-2 and Characterise Omicron-Specific Reactivity in a Vaccination Cohort - Michael Schoefbaenker; Rieke Neddermeyer; Theresa Guenther; Marlin M. Mueller; Marie-Luise Romberg; Nica Classen; Marc T. Hennies; Eike R. Hrincius; Stephan Ludwig; Joachim E. Kuehn; Eva U. Lorentzen (Vaccines, 2023)
Virus-specific antibodies are crucial for protective immunity against SARS-CoV-2. Assessing functional antibodies through conventional or pseudotyped virus neutralisation tests (pVNT) requires high biosafety levels. Alternatively, the virus-free surrogate virus neutralisation test (sVNT) quantifies antibodies interfering with spike binding to angiotensin-converting enzyme 2. We evaluated secreted nanoluciferase-tagged spike protein fragments as diagnostic antigens in the sVNT in a vaccination cohort. Initially, spike fragments were tested in a capture enzyme immunoassay (EIA), identifying the receptor binding domain (RBD) as the optimal diagnostic antigen. The sensitivity of the in-house sVNT applying the nanoluciferase-labelled RBD equalled or surpassed that of a commercial sVNT (cPass, GenScript Diagnostics) and an in-house pVNT four weeks after the first vaccination (98% vs. 94% and 72%, respectively), reaching 100% in all assays four weeks after the second and third vaccinations. When testing serum reactivity with Omicron BA.1 spike, the sVNT and pVNT displayed superior discrimination between wild-type- and variant-specific serum reactivity compared to a capture EIA. This was most pronounced after the first and second vaccinations, with the third vaccination resulting in robust, cross-reactive BA.1 construct detection. In conclusion, utilising nanoluciferase-labelled antigens permits the quantification of SARS-CoV-2-specific inhibitory antibodies. Designed as flexible modular systems, the assays can be readily adjusted for monitoring vaccine efficacy.